Scattered data interpolation using combination method of triangular patches - Saaban, Azizan; Ahmad, Nazihah; Hassan, Mohammad Hasnan; Mansor, Kamarun Hizam; Mohamad, Mohd Saiful Adli; Mohd Alifiah, Fathilah; Khalid, Kamal (UUM Press, 2012)
This monograph is a comprehensive report on scattered data interpolation using combination method of triangular patches where the interpolating surface comprise the combination of quintic Hermite and interior interpolation operators.It is based on the findings of a university grant research project sponsored by Universiti Utara Malaysia. In particular, the contents of this monograph are useful for students and researchers especially in the area of Computer Aided Geometric Design (CAGD) and generally the contents will also benefit academicians as well as practitioners who have interest in the application of the triangulation based interpolation method in real world problems.